Relationship of the GRDP Sectors with Environmental Quality Index in Indonesia 2012-2017 - Ummi, Izzatul; Rusdarti, Rusdarti; Yanto, Heri (Journal of Economic Education, 2019)
The purpose of this research are to find out and analyze the relationship between the agricultural sector, the mining sector, the manufacturing sector, the construction and transportation sectors with the environmental quality index in Indonesia.This study used a quantitative method derived from secondary data in the form of publication data of the GRDP sectors on constant prices and environmental quality indices in 33 provinces on an annual basis in 2012-2017. The population in this study are the GRDP in Indonesia and statistics on environmental quality indexes in Indonesia. Data analysis used panel data regression analysis with fixed effect regression models used eviews 9 tools. The results shows partially agriculture and transportation sector variables have a positive and significant relationship with the environmental quality index (EQI), while the mining and construction sector variables have a negative and significant relationship, while manufacturing industries variables have a negative and insignificant relationship. Variables in the agriculture sector, the mining sector, the manufacturing sector, the construction sector, and the transportation sector together have a positive and significant relationship with the environmental quality index (EQI).